Associations of cognitive dysfunction with motor and non-motor symptoms in patients with de novo Parkinson’s disease - Kyum-Yil Kwon; Suyeon Park; Rae On Kim; Eun Ji Lee; Mina Lee (Scientific Reports, 2022)
Abstract The risk factors of mild cognitive impairment (MCI) in patients with de novo Parkinson’s disease (PD) remain unclear. Therefore, the objective of this study was to compare motor and non-motor symptoms between de novo patients with PD with and without MCI. Moreover, detailed relationships between each cognitive deficit and other clinical characteristics in de novo patients with PD were investigated. Consecutive patients with de novo PD were retrospectively enrolled in this study. Motor symptoms were assessed using the Unified Parkinson’s Disease Rating Scale (UPDRS) part-III and the Hoehn and Yahr (HY) stage. Non-motor symptoms including depression, anxiety, fatigue, and autonomic dysfunction were measured using representative questionnaires. Motor symptoms, depression, and dysautonomia were associated with MCI in de novo patients with PD. Compared with the non-MCI group with PD, the MCI group with PD had higher scores of UPDRS-III, HY stage, depression, and dysautonomia, but not fatigue or anxiety. Both UPDRS-III and HY stage were significantly linked to all cognitive deficits except attention. Logistic regression analysis showed that depression was associated with memory, visuospatial, and executive impairment, and dysautonomia was related to visuospatial and executive impairment. The results of this study suggest that cognitive impairment in PD might have a different relationship pattern to the motor and some non-motor symptoms.